The efficacy of mindfulness-based interventions for patients with COPD: a systematic review and meta-analysis protocol. Issue 5 (28th May 2019) - Tian, Lingyun; Zhang, Ying; Li, Li; Wu, Ying; Li, Yinglan
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is a common chronic respiratory disease. It has adverse effects on patients' physical health, mental well-being and quality of life. The purpose of mindfulness-based interventions (MBIs) is to raise non-judgemental awareness and attention to current internal and external experiences. This means the attention is shifted from perceived and involuntary inner activities to current experience, keeping more curious, open and accepting attitudes towards current experience. Although some studies on the intervention effect of MBIs in patients with COPD have been conducted, the results are controversial, especially on dyspnoea, level of mindfulness and quality of life. Therefore, a systematic review of MBIs in patients with COPD is required to provide available evidence for further study. Methods and analysis: In this study, different studies from various databases will be involved. Randomised controlled trials(RCTs)/quantitative studies, qualitative studies and case studies on the effect of MBIs in patients with COPD aged over 18 years will be included. We will search the literature in the databases of PubMed, Excepta Medica Base (EMBASE), Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), the Cochrane Library, PsycINFO and China National Knowledge Infrastructure(CNKI). The primary outcomes will include efficacy of MBIs for patients with COPD in terms of dyspnoea, depression and anxiety. The secondary outcomes will include efficacy of MBIs in terms of quality of life, mindful awareness, 6-minute walk test(6MWT) and nutritional risk index. Data extraction will be conducted by two researchers independently, and risk of bias of the meta-analysis will be evaluated based on the Cochrane Handbook for Systematic Reviews of Interventions. All data analysis will be conducted by data statistics software Review Manager V.5.3. and Stata V.12.0. Ethics and dissemination: Since this study is a systematic review, the findings are based on the published evidence. Therefore, examination and agreement by the ethics committee are not required in this study. We intend to publish the study results in a journal or conference presentations. PROSPERO registration number: CRD42018102323.